Relationship between Skin Transplantation Immunity and the Formation of Humoral Isoantibodies in Mice - Hildemann, W. H. (1959)
Crude splenic nuclear fractions can incite skin transplantation immunity in mice without producing a detectable titre of haemagglutinins or haemolysins, and have little if any power to absorb antibodies from sera in which they have been caused to appear by other means. Antigenic preparations of other kinds can incite iso-antibody formation unaccompanied by transplantation immunity. Thus humoral iso-antibodies can be present when transplantation immunity is absent and absent when it is present. Transplantation immunity and serum antibody production probably depend upon different immunological processes, even if they eventually prove to be elicited by antigens with the same or similar determinant groups.